Adoption of National Language for Teaching and Learning Vocational Education for Sustainable Devlopment In Nigeria - Yusuf, S. S.; Muhammad, , Z. R.,; Ukwumaka, K. O.; Haliru, A.; Duze, , D. A. (Kashere Journal of Education, 2021)
Naturally, language is the human vocal sounds or the arbitrary graphic representation of these sounds in writing used systematically and conventionally bya speech community for the purposes of communication, Osinsanyo (2007). On the other hand, education is seen as the overall round development of individuals, their economic, cultural and spiritual being. The process of molding and shaping personality is facilitated through the use of language as a vehicle; language plays vital roles in most known formal educational systems. This paper among other things discuss the concept of language education, proficiency, vocational achievement, vocational trainning, multilingualism and its challences, language skills in vocational education and sustainable national development. It features as a subject in the school curriculum and is used to serve as the medium of instruction in all the subjects globally. Thus, this paper seeks to consider ‘adoption of national language education for sustainable development in Nigeria’ and made the following recommendations: There is the need to develop a good language education programme for vocational school level in Nigeria ,Teachers should jointly help the pupils to develop competence in the use of their language and that of the immediate environment of schooling, and the government should make adequate funds available for the provision of regular and intensive professional capacity development for classroom teachers in the Universal Basic Education.